1992
DOI: 10.1073/pnas.89.8.3571
|View full text |Cite|
|
Sign up to set email alerts
|

Lipocortin 1 mediates dexamethasone-induced growth arrest of the A549 lung adenocarcinoma cell line.

Abstract: Pharmacology. In the article "Lipocortin 1 mediates dexamethasone-induced growth arrest of the A459 lung adenocarcinoma cell line" by J. D. Croxtall and R. J. Flower, which appeared in number 8, April 15, 1992, of Proc. Natl. Acad. Sci. USA (89,(3571)(3572)(3573)(3574)(3575)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
95
1
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 42 publications
6
95
1
2
Order By: Relevance
“…39 It has also been found that the addition of glucocorticoid, an anti-inflammatory agent, to A549 cells results in annexin-I translocation to the membrane compartment and subsequent externalization: the membrane-bound protein inhibited prostaglandin release by affecting cytosolic phospholipase A 2 activation through an effect of epidermal growth factor signaling, thereby blocking cell proliferation. 17,40 Although our study shows a direct effect of annexin-I expression in actin remodeling in response to GTE, one cannot exclude the possibility of such an observed effect being a secondary event, for example, as the result of cellular anti-inflammatory response as observed for glucocorticoid. Whereas annexin-I specific RNA interference blocks the GTE-induced actin polymerization and adhesion, the effect of such interference on cell motility is complicated by the finding that siRNA Immunofluorescence analysis of paxillin in A549 cells treated with 40 mg/ml of GTE for 24 h were washed, fixed, and labeled with paxillin (red fluorescence), as detailed in the Materials and methods section.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…39 It has also been found that the addition of glucocorticoid, an anti-inflammatory agent, to A549 cells results in annexin-I translocation to the membrane compartment and subsequent externalization: the membrane-bound protein inhibited prostaglandin release by affecting cytosolic phospholipase A 2 activation through an effect of epidermal growth factor signaling, thereby blocking cell proliferation. 17,40 Although our study shows a direct effect of annexin-I expression in actin remodeling in response to GTE, one cannot exclude the possibility of such an observed effect being a secondary event, for example, as the result of cellular anti-inflammatory response as observed for glucocorticoid. Whereas annexin-I specific RNA interference blocks the GTE-induced actin polymerization and adhesion, the effect of such interference on cell motility is complicated by the finding that siRNA Immunofluorescence analysis of paxillin in A549 cells treated with 40 mg/ml of GTE for 24 h were washed, fixed, and labeled with paxillin (red fluorescence), as detailed in the Materials and methods section.…”
Section: Discussionmentioning
confidence: 82%
“…They are either found free in the cytosol or associated with membranes of various cell types and tissues including the lung. Annexin-I is the first of 13 members in the family and is involved in many biological functions such as cell differentiation, 35 anti-inflammation, 36 apoptosis, 37 and cell growth, 17 and acts as a stress protein. 38 Annexin-I has been studied for its role in stimulating actin polymerization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mAb, 1-B (5,19), was used to block biological activities of ANX1. Ab against the ␣ 4 integrin (FITC-conjugated CD49d mAb, diluted 1/20) was from Immunotech (Luminy, France).…”
Section: Abs Recombinant Proteins and Peptidesmentioning
confidence: 99%
“…Maturation of blood leukocytes to tissue macrophages may influence the steroid sensitivity of LC-1 expression, as glucocorticoid-induced increases in LC-1 in alveolar macrophages, although not in blood leukocytes, are accompanied by inhibition of prostaglandin E2 (PGE2) release (De Caterina et al, 1993). Other studies have implicated LC-1 in glucocorticoid suppression of PGE2 release from macrophages (Flower, 1988) and the A549 human adenocarcinoma cell line (Croxtall & Flower, 1992;1994). Transfection of A549 cells with antisense DNA for an N-terminal portion of LC-1 not only blocks glucocorticoid suppression of PGE2 release, but also prevents the glucocorticoid-induced cell surface expression of newly synthesized LC-1 .…”
Section: Introductionmentioning
confidence: 99%